Metabolic Resource Allocation in Individual Microbes Determines Ecosystem Interactions and Spatial Dynamics - William R. Harcombe; William J. Riehl; Ilija Dukovski; Brian R. Granger; Alex Betts; Alex H. Lang; Gracia Bonilla; Amrita Kar; Nicholas Leiby; Pankaj Mehta; Christopher J. Marx; Daniel Segrè (Cell Reports, 2014)
The interspecies exchange of metabolites plays a key role in the spatiotemporal dynamics of microbial communities. This raises the question of whether ecosystem-level behavior of structured communities can be predicted using genome-scale metabolic models for multiple organisms. We developed a modeling framework that integrates dynamic flux balance analysis with diffusion on a lattice and applied it to engineered communities. First, we predicted and experimentally confirmed the species ratio to which a two-species mutualistic consortium converges and the equilibrium composition of a newly engineered three-member community. We next identified a specific spatial arrangement of colonies, which gives rise to what we term the “eclipse dilemma”: does a competitor placed between a colony and its cross-feeding partner benefit or hurt growth of the original colony? Our experimentally validated finding that the net outcome is beneficial highlights the complex nature of metabolic interactions in microbial communities while at the same time demonstrating their predictability. Video Abstract: